A molecular phylogeny of chafers revisits the polyphyly of Tanyproctini (Scarabaeidae, Melolonthinae). (10th March 2019) - Eberle, Jonas; Sabatinelli, Guido; Cillo, Davide; Bazzato, Erika; Šípek, Petr; Sehnal, Richard; Bezděk, Aleš; Král, David; Ahrens, Dirk
Abstract: Tanyproctini (Melolonthinae) is a large group of chafers within the pleurostict Scarabaeidae that shows an enormous morphological diversity and variation. However, their morphology based definition appears to be mainly based on presumably plesiomorphic characters. Here, we investigate the phylogeny of this interesting lineage with a three‐gene data set using partial gene sequences of 28S rRNA, cytochrome c oxidase I (cox1) and 16S rRNA (rrnL). Our data set comprised 191 species of all major lineages of pleurostict scarabs. Combined analyses of the 2, 070 base pairs alignment with maximum‐likelihood and Bayesian tree inference always recovered Tanyproctini to be highly polyphyletic. Tests of an alternative topology with constrained monophyly of Tanyproctini using CONSEL and IQ‐TREE were not found to be more likely than the unconstrained tree topology. Instead, Tanyproctini was split into six independent lineages under the current taxon sampling that were scattered throughout diverse parts of the pleurostict tree. The fact that numerous smaller chafer lineages exist beside several evolutionary successful and large lineages, highlights the complexity of the pleurosticts' evolutionary history. The resulting tree topologies imply the need for a thorough revision of tribal classification within Melolonthinae lineages to accommodate the polyphyly of Tanyproctini. However, a revision of classification would be premature due to low support of most relevant branches, instable tree topologies among different tree searches, and due to a still very incomplete representation of Tanyproctini lineages.